Industrial connector sets and interconnect components to be used in optical fibre control and communication systems. Product specifications. Type ODVA APC terminated on EN 60793-2-50 category B1.1 and B1.3 singlemode fibre to meet the requirements of category I (industrial environments) as specified in EN 50173-1 and IEC 61753-1-3 Part 3-1, (30th June 2014) - British Standards Institution,
No abstract available